Inovasi UMKM Pendukung Rintisan Wisata Trabas Desa Polosiri Bawen Kabupaten Semarang - Nila Kusumaningtyas; Sudargo Sudargo; Sutomo Sutomo; Yuris Setyoadi; Mega Novita (Journal of Dedicators Community, 2021)
Polosiri is a village located in Bawen District, Semarang Regency. Since 2019, Polosiri has been accompanied by Universitas PGRI Semarang (UPGRIS) and Universitas Darul Ulum Islamic Centre Sudirman (UNDARIS) University to pioneer a trabas-themed tourism village. But in 2020, due to the Covid-19 pandemic, the community service activities will be focused on strengthening KWT Lestari Sejahtera as a unit that will support the trabas-themed tourism village. Even though they already have a brand product, their business management and the production capacity were yet maximized. Assistance is needed to innovate in many aspects such as product diversification, production-process innovation and marketing innovation. The method used in this work is community development which places citizens as both object and subject. Various appropriate technologies such as Bimo-CF starter the key point to make mocaf, automatic cassava cutting machine, automatic flour powder machine, continuous sealer machine are adopted